Relationships between Problematic Cannabis Use and Risky Behaviors in Spanish Adolescents - Alarcó-Rosales, Raquel (Int J Environ Res Public Health, 2019)
This study examined the relations between problematic cannabis use, physical assault, and getting involved in a motor vehicle accident under the influence of cannabis in a sample of adolescents randomly selected from 25 public and semiprivate high schools in Alicante (Spain). Participants (n = 648) completed The Spanish National Standardized Survey about drug use in high school adolescents (ESTUDES, 2017), which includes the cannabis abuse screening test (CAST). Prevalence of cannabis use across the life-span and within the past 30 days was 37.5% and 17.4%, respectively. CAST scores were associated with an increased risk of driving under the effects of cannabis, riding shotgun, and physical assault, but not with an increased risk of having a motor vehicle accident. There were no differences between boys and girls in the association of problematic cannabis use with risky behaviors. This result highlights the importance of comprehensive prevention and education strategies for adolescents at high risk of cannabis use.